Knockdown of GBP5 alleviates renal damage caused by psoriasis by regulating NF-κB/STAT3 pathway - Ren, Fang; Li, Jin; Ni, Xingyan; Yuan, Hongshan; Yan, Wenliang (Allergologia et Immunopathologia, 2024)
Background: Kidney impairment resulting from psoriasis constitutes a serious complication, affecting the overall well-being of patients and necessitating a thorough comprehension for efficient management. Guanylate-binding protein 5 (GBP5) is known to play a role in inflammatory responses, but its function in psoriasis remains unclear and warrants investigation in. Objective: To pinpoint GBP5 as innovative therapeutic target and decipher the underlying mechanisms in kidney impairment resulting from psoriasis. Methods: Skin samples from psoriatic patients were used to detect GBP5 expression through Immunoblot and qPCR. Hacat cells were treated with TNF-α to construct the psoriasis skin cell model. Edu and CCK-8 assays were performed to confirm the effects on cell viability, ELISA was conducted to confirm the effects on inflammation. H&E staining and PASI scocing were conducted to confirm the effects on renal damage. Immunoblot confirmed the mechanism. Results: GBP5 was highly expressed in psoriasis skin tissues. Ablation of GBP5 reduced tumor necrosis factor alpha (TNF-α)-stimulated growth as well as inflammation in human immortalized keratinocyte (HaCaT) cell. In the imiquimod (IMQ)-stimulated mouse model, GBP5 knockdown alleviated psoriasis symptoms and reduced renal damage. Mechanically, GBP5 depletion suppressed the activation of nuclear factor kappa-light-chain-enhancer of activated B cells–signal transducer and activator of transcription 3 (NF-κB/STAT3) axis. Conclusion: Inhibiting GBP5 can mitigate the renal injury caused by psoriasis through NF-κB/STAT3 axix.